Replacing single missing teeth in the posterior region using direct composite restorations: Survival and clinical quality. (October 2021) - Staehle, Hans Joerg; Sekundo, Caroline; Hieronymus, Hanna; Büsch, Christopher; Frese, Cornelia
Abstract: Objectives: The aim of this pilot study was to test the survival and clinical quality of frugal methods to replace single missing teeth in the posterior region with direct composite restorations of different categories. Methods: We performed a detailed intraoral examination and assessed the clinical quality of the restorations according to modified FDI-criteria. Irreparable loss of a restoration was recorded as "failure" (F). Damaged restorations that could be repaired were defined as "survival with repair" (SR). Restorations without any unfavorable events were classified as "success" (S). Results: The mean follow-up time of the restorations was 5.07 years (minimum = 1; maximum = 21.5), with 15.1% having a follow-up time of more than 10 years. Three unfavorable events were documented. Two restorations (3.8%) were classified as F, one restoration (1.9%) as SR, and the remaining 50 restorations (94.3%) as S. The estimated overall and functional survival rate at 5 years using the Kaplan-Meier method was 96.2% (confidence interval [CI]:85.5% to 99%) and 98% (CI:86.9% to 99.7%), respectively. Ninety-four percent of the restorations were evaluated as good or excellent clinical quality. Most restorations showed no periodontal complications, however, restorations in the mandible showed significantly more plaque accumulation (p=0.002). Conclusions: These conservative frugal methods to replace single missing teeth in the posterior region showed promising clinical survival data and quality parameters. Clinical significance: Direct composite restorations of different categories can be considered as additional treatment option for gap closure in specific clinical situations.